The Patristic Book of Nature: A Shared Spiritual Resource between East and West - Juurikkala, Oskari (Teresianum, 2025)
Abstract This article outlines the patristic understanding of the book of nature. It highlights the ideas of the logoi of creation and the contemplation of nature as the basis for the Fathers’ theology of nature as a divine book. It explores a variety of themes in the book of nature, especially the knowledge of God and the use of nature as a place of loving dialogue with God. It finally argues that the book of nature is not a sufficient principle on its own and explains how this affects the patristic understanding of natural law. The article ends by showing how the liturgical orientation of nature is another way in which nature and Scripture are parallel principles that are called to transcend their own limitations and find their fullness in Christ.